Optimalisasi Penyaluran Zakat dalam Perspektif Maqashid Syariah: Analisis Hukum Islam terhadap Model dan Efektivitas Pemberdayaan Mustahik - Hafizan Adhimllah; Yudi Gunawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Zakat plays a strategic role in the Islamic economic system as an instrument for wealth redistribution aimed at achieving social justice and sustainable welfare. This study examines the optimization of zakat distribution from the perspective of maqashid shariah through a normative legal analysis of Islamic law and the effectiveness of mustahik empowerment models. The research focuses on evaluating whether zakat distribution practices align with the objectives of protecting religion, life, intellect, lineage, and property. Using qualitative library research, this study analyzes various models of productive zakat implemented by zakat institutions and assesses their impact on the socio-economic welfare of mustahik. The findings indicate that zakat programs oriented toward empowerment, supported by strong governance, continuous assistance, and clear performance indicators based on maqashid shariah, tend to produce more sustainable outcomes. However, challenges remain in standardizing evaluation mechanisms and ensuring long-term program sustainability. This study concludes that integrating maqashid shariah into zakat management policies is essential to enhance effectiveness, accountability, and social impact. The results are expected to contribute to the development of more equitable and transformative zakat governance in Indonesia.